(untitled) (Journal of Plant Disease Sciences, 2017)
Horticultural crops being intensive play an important role in countries’ economy through employment generation and improving farm income. Among different temperate fruits, apple ( x Malus domestica Borkh.) is the most important crop of the world and is cultivated on an area of 5,051,851 ha with an annual production and productivity of 84,630,275 T and 16.75 MT/ha, respectively (FAO, 2014). India ranks 5 in production of apple in the world with an th area of about 3,13,040 ha and an annual production and productivity of 2497,680 MT and 7.97 MT/ha respectively (FAO, 2014). In Himachal Pradesh apple is being cultivated over 1,10,679 ha with annual production of 7,77,126 MT (Annoymous, 2016). Whereas, in dry temperate zone of Himachal Pradesh apple is cultivated over 12,506 ha with an a n n u a l p r o d u c t i o n o f 5 9 , 4 7 3 M T (Annonymous, 2015). Though, cultivation of apple has revolutionized the socio-economic status of farmers of tribes of Himachal Pradesh, yet the productivity of apple is very low 4.76 MT/ha (Anonymous, 2015) is relatively low in comparison to global productivity of 16.75 MT/ha. Different factors are responsible for low productivity of apple, among these diseases play an important role. Apple crop falls prey to wide range of fungal, bacterial and viral pathogens, where, viral diseases need greater attention for being its systemic nature that passes to the successive generations through clonal propagation, thus causing decline of trees. Latent viral infection goes unnoticed and gradually results in the loss of plant vigour, reduction in quality of produce as well as yield of the crop.